2019
DOI: 10.1096/fj.201802145rr
|View full text |Cite
|
Sign up to set email alerts
|

TRB3 regulates skeletal muscle mass in food deprivation–induced atrophy

Abstract: Tribbles 3 (TRB3) is a pseudokinase that has been found in multiple tissues in response to various stress stimuli, such as nutrient deprivation and endoplasmic reticulum (ER) stress. We recently found that TRB3 has the potential to regulate skeletal muscle mass at the basal state. However, it has not yet been explored whether TRB3 regulates skeletal muscle mass under atrophic conditions. Here, we report that food deprivation for 48 h in mice significantly reduces muscle mass by ∼15% and increases TRB3 expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…43 To stimulate ribophagy and muscle wasting, myotubes were maintained in differentiation medium (DM), incubated with tumor conditioned media (CM) from confluent ES-2 culture plates, or switched to PBS to promote nutrient deprivation-induced autophagy and myotube atrophy. 44,45 Autophagy was blocked by incubating myotubes with Chloroquine diphosphate salt (CLQ) (MP Biomedicals, Santa Ana, CA) in DMSO at 25 µM concentration for 24 hours before replacing the media with CLQ in DM (DM + CLQ) or PBS (PBS + CLQ) for an additional 1 hour and 6 hours In separate experiments, we inhibited ubiquitin-mediated proteolysis by treating myotubes with the reversible proteasome inhibitor Carbobenzoxy-Leu-Leu-Leucinal (MG-132) at 25 µM alone, or in combination with CLQ for 6 hours without CLQ pretreatment.…”
Section: Animal Model Of Ovarian Cancer and Cell Culture Experimentsmentioning
confidence: 99%
“…43 To stimulate ribophagy and muscle wasting, myotubes were maintained in differentiation medium (DM), incubated with tumor conditioned media (CM) from confluent ES-2 culture plates, or switched to PBS to promote nutrient deprivation-induced autophagy and myotube atrophy. 44,45 Autophagy was blocked by incubating myotubes with Chloroquine diphosphate salt (CLQ) (MP Biomedicals, Santa Ana, CA) in DMSO at 25 µM concentration for 24 hours before replacing the media with CLQ in DM (DM + CLQ) or PBS (PBS + CLQ) for an additional 1 hour and 6 hours In separate experiments, we inhibited ubiquitin-mediated proteolysis by treating myotubes with the reversible proteasome inhibitor Carbobenzoxy-Leu-Leu-Leucinal (MG-132) at 25 µM alone, or in combination with CLQ for 6 hours without CLQ pretreatment.…”
Section: Animal Model Of Ovarian Cancer and Cell Culture Experimentsmentioning
confidence: 99%
“…Knockdown of TRIB3 in skeletal muscle improved insulin sensitivity in a rat model for insulin resistance (Weismann et al, 2011); however, rats exposed to short-term exercise training improved glucose tolerance without changes in skeletal muscle TRIB3 protein (Canciglieri et al, 2018). TRIB3 has also been implicated in the regulation of muscle mass, as well as exercise capacity (An et al, 2014;Choi et al, 2019); however, RNA-sequencing data we have collected from human vastus lateralis muscle demonstrates that TRIB1 is the predominant form expressed in human muscle with minimal expression of TRIB3 (data not shown). Therefore, these observations indicate that alterations in TRIB1 expression may be involved in the adaptation to exercise in human skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that TRB3 caused muscle fiber atrophy and a decrease in muscle function by negatively modulating protein turnover in the condition of food deprivation (Choi et al, 2017(Choi et al, , 2019 and could inhibit the myogenic differentiation of C2C12 (mouse myoblast) cells (Kato & Du, 2007). Shang et al acquired TRB3 knockout mice and found that sarcopenia was attenuated in these mice compared with aged controls via the alleviation of atrophy and fibrosis of skeletal muscles (Shang et al, 2020 As noted below, in C. elegans (Depuydt et al, 2013;Duhon & Johnson, 1995;Herndon et al, 2002) and in Drosophila (Demontis & Perrimon, 2010;Owusu-Ansah, Song, & Perrimon, 2013), genetic reduction in the insulin/IGF1 signaling pathway, which causes increased nuclear translocation of DAF-16 (FOXO in mammals), results in lifespan extension and reduced sarcopenia in these organisms.…”
Section: Molecular Discoveriesmentioning
confidence: 99%
“…TRB3 was previously reported to exhibit an age‐related increase in expression (Meyer, Schenk, & Lieber, 2013) and play a vital role in cell proliferation, differentiation, and fibrosis. It has been demonstrated that TRB3 caused muscle fiber atrophy and a decrease in muscle function by negatively modulating protein turnover in the condition of food deprivation (Choi et al, 2017, 2019) and could inhibit the myogenic differentiation of C2C12 (mouse myoblast) cells (Kato & Du, 2007). Shang et al acquired TRB3 knockout mice and found that sarcopenia was attenuated in these mice compared with aged controls via the alleviation of atrophy and fibrosis of skeletal muscles (Shang et al, 2020).…”
Section: Rodentsmentioning
confidence: 99%